Comparative Conclusions - Jauslin, Daniel (A+BE | Architecture and the Built Environment, 2019)
In the first section of this last chapter (7.1.) I will “comparatively” answer the main question related to each case before coming to broader discussion (7.2.) all of which contributes the the main question: In what way do landscape design strategies change how we understand and create architecture? (Q 1.1.1.) At first I differentiate the motives and objectives for landscape strategies in the specific context of each of the three study cases in chapters 4, 5 & 6 to discuss the development of landscape design strategies in architecture: How do architects apply landscape design strategies in architecture? What are their motives and goals to do so and what do they accomplish? (Q. 1.1.3.) In terms of spatial contexts the projects are quite different. In particular, the dense urban situation with a long history dating back centuries in Paris; the implementation in a modern campus in Lausanne; and the placement outside Santiago with historical reference to the early medieval city are three completely different project contexts. In terms of surrounding landscapes, the riverside urban development of Paris; the large plateau above the lake Geneva; and Monte Gaiás across the valley from Santiago pose different landscape relations.